The combined effects of exercise and music on sports anxiety, exercise beliefs, coping effectiveness, and mental toughness among chinese college students with sports anxiety - Zhutang, Liu (2025)
Sports anxiety is a worldwide concern that impacts athletes’ performance and discourages non-athletes from participating in sports. In China, with a population exceeding 1.4 billion and an increasing emphasis on physical education in the school curriculum, students are encountering growing challenges related to sports participation. This study comprises two phases. The aim of Phase 1 is to examine the validity and reliability of the Chinese-translated versions of the Physical Education State Anxiety Scale (PESAS), the Exercise Beliefs Questionnaire (EBQ), the Coping Effectiveness (CE) scale, and the Mental Toughness for Youth Questionnaire (MTYQ) utilizing Confirmatory Factor Analysis (CFA) and internal consistency reliability assessments. Additionally, Phase 1 aims to construct a Structural Equation Modelling (SEM) to explore the relationships among sports anxiety, exercise beliefs, coping effectiveness, and mental toughness in Chinese university students with sports anxiety. A total of 1,055 participants completed the questionnaires, of which 755 responses were valid. According to the research results, the final SEM of phase 1 has a good model fitting index: comparative fit index (CFI)=0.926, tucker lewis index (TLI) = 0.923, standardised root means square residual (SRMR) = 0.029, root mean square error of approximation (RMSEA) (90% CI) = 0.045 (0.041, 0.048), RMSEA p-value < 0.001. The 6 SEM specific hypotheses (2 additional alternative hypotheses and 4 hypotheses from the initial model) were produced a significant interrelationship with cognitive processes (CP), coping effectiveness (CE), somatic anxiety (SA), exercise beliefs (EB), and mental toughness (MT) in the final SEM. CE and CP were constructs that directly affected MT. The objective of Phase 2 is to investigate time effects, group effects, and time*group effects between experimental and control groups of Chinese university students with sports anxiety. The exercise intervention consisted of an intensity of at least 50% to 60% of the average maximum heart rate, progressing by 5% every four weeks. For the music intervention, tracks with a tempo range of 110–120 beats per minute were selected. The combination of music and exercise interventions were conducted simultaneously. A total of 108 university students with sports anxiety were randomly assigned to two groups. The intervention lasted for 12 weeks, with sessions conducted three times a week, each lasting 40 minutes. Participants completed the PESAS, EBQ, CE, and MTYQ at four time points: one week before the intervention, during the intervention at four weeks, during the intervention at eight weeks, and after the intervention at twelve weeks. According to the research results of phase 2, experimental group significantly exhibited the higher scores than the control group on sports anxiety, exercise beliefs, mental toughness, and coping effectiveness with respectively p-values =0.001, =0.046, =0.022, <0.001. The music and exercise intervention has a positive impact on sports anxiety SA, SB, MT, and CE among Chinese university students with sports anxiety. The research findings contribute to the diversity of measurement tools for assessing SA, sports anxiety, EB, CE, and MT in the Chinese context, offering effective instruments for advancing psychological research in China